Peran Infrakstruktur Pendukung Bagi Penyandang Disabilitas Tuna Netra - Anis Kumalasari; Fayza Jasmine Oktaferly; Didit Kurniawan Wintoko (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
People with disabilities often get low social stigma in the social environment. Persons with disabilities are often marginalized from the general public, this is because persons with disabilities are considered to lack abilities that are equal to non-disabled people. As people with disabilities, they also have the same rights as society in general, namely the right to get access to education, access to infrastructure and access to other public services that can be accessed easily. but on the other hand until now there are still many persons with disabilities who still do not get their rights. one of them is the right to get access to infrastructure such as road access, easy access to open facilities, this is caused by several factors, one of which is the design made on infrastructure that is less accessible for persons with disabilities. in this study aims to see how accessibility is fulfilled, especially in public facilities provided to persons with disabilities in the city of Jember. This research method uses descriptive qualitative using social construction theory. As for data collection in research through field observations and also interviews besides that it is also supported by literature studies. The results obtained in this study show that public facilities for blind persons with disabilities in the city of Jember are still not friendly for blind persons with disabilities to access.